Comprehensive investigation on the mechanical properties of friction stir composite joint from polyethylene-polypropylene. (2018) - Mojtaba, Rezaee Hajideh; Farahani, Mohammadreza; Shapurgan, Omid
The widespread application of polymers has motivated researchers to improve their forming and joining processes. In this category, friction stir welding (FSW) proposed as an alternative for the traditional joining processes. In this paper, FSW with a threaded cylindrical tool was employed for dissimilar joining of sheets of polyethylene and polypropylene. In order to control the material flow, the used tool was equipped with a hot shoe. In the following, the influences of important process parameters such as tool rotation speed, tool traverse speed and tool tilt angle on the joint mechanical properties were investigated. In the optimum joining condition, composite welded joint with defect-free uniform microstructure, with strength equal to 99% of polyethylene and with higher elongation and hardness than the polyethylene was obtained. The optimum rotational speed equal to 1, 860 rpm with the highest travel speed equal to 12.5 mm/min provide the welded joints with best mechanical properties. [Submitted 4 April 2017; Accepted 29 August 2017]